Referral of patients with primary biliary cirrhosis for liver transplantation. Issue 9 (September 1990) - Neuberger, J M; Gunson, B K; Buckels, J A; Elias, E; McMaster, P
Abstract : All patients with primary biliary cirrhosis referred to this unit for consideration for transplantation between April 1981 and January 1989 were analysed retrospectively to assess whether disease stage at referral affects the outcome after grafting and whether greater awareness of the benefits of the procedure means that patients are now being referred at an earlier stage. Seventy of the 107 patients have been grafted, with an overall one year actuarial survival of 62%. A better prognosis at the time of referral, as assessed by both serum bilirubin concentration and a mathematically derived prognostic index, was associated with a greater probability of survival after grafting. Patients in the tertile with the best prognosis (median serum bilirubin concentration at referral 84 mumol/l and estimated survival in the absence of transplantation of more than nine months) had a 78% one year actuarial survival after transplantation, whereas those in the tertile with the worst prognosis (median serum bilirubin concentration 467 mumol/l and estimated survival of less than four months) had a one year actuarial survival of only 50%. No trend towards earlier referral of patients, however, was shown using either of these two markers. This retrospective analysis suggests that many patients are being referred too late for an optimal outcome. We recommend that patients with primary biliary cirrhosis who are potential candidates for liver grafting should be referred to a transplant centre before the serum bilirubin concentration approaches 150 mumol/l.